Report of the Task Force on Agrarian Relations - Planning Commission (Planning Commission, 1973)
Laws imposing ceiling on agricultural holdings have been enacted in all the States except the former Punjab areas of Haryana and Punjab, where the State Government has powers to settle tenants to lands held by owners in excess of the permissible limit. However, as a result of the high level of ceiling, large number of exemptions from the law, malafide transfers and partitions, and poor implementation the results achieved have been meagre. So far only about one million hectares of land has been declared surplus.
Planning Commission
Planning Commission